Fiabe resiane = Rezijanske pravljice = Pravice po rozajanskin Dall'archivio dell'Istituto di etnologia slovena ZRC SAZU e dalla raccolta privata di Roberto Dapit = Iz arhiva Inštituta za slovensko narodopisje ZRC SAZU in privatne zbirke Roberta Dapita - Dapit, Roberto; Matičetov, Milko (ZRC SAZU, Založba ZRC, 2014)
Presented are seven folktales from Resia in northern Italy with a strong Slovene minority. On CD are presented narratives which have been recorded on magnetic tape by Academician Milko Matičetov. Translations from the Resian dialect in Slovene and in Italian language are published in accompanying book. One folk tale was recently recorded by Roberto Dapit in the Resian village of Lischiazze/Liščaci, and has been included in the collection to illustrate contemporary Resian narrative tradition. The tales recorded on the compact disk represent four different language groups of the Resian dialect, namely that of Stolvizza/Solbica, Oseacco/Osojane, San Giorgio/Bila, and Gniva/Njiva. This work was done within the project Zborzbirk.